2018
DOI: 10.1002/ange.201809343
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Atomic Dispersion of Highly Loaded Transition Metals in Small‐Pore Zeolite SSZ‐13: High‐Capacity and High‐Efficiency Low‐Temperature CO and Passive NOx Adsorbers

Abstract: The majority of harmful atmospheric CO and NOx emissions are from vehicle exhausts. Although there has been success addressing NOx emissions at temperatures above 250 °C with selective catalytic reduction technology, emissions during vehicle cold start (when the temperature is below 150 °C), are a major challenge. Herein, we show we can completely eliminate both CO and NOx emissions simultaneously under realistic exhaust flow, using a highly loaded (2 wt %) atomically dispersed palladium in the extra‐framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(107 citation statements)
references
References 56 publications
5
101
0
Order By: Relevance
“…11). It was previously shown by us that Pd(II)-NO in SSZ-13 upon CO adsorption selectively forms Pd(II)(CO)(NO) complex [8,11] largely responsible for excellent performance of Pd(II)/SSZ-13 as a low temperature passive NOx adsorber (at 100 ⁰C). However, in this case, we observe the unselective formation of Pd(II)(CO)(NO) even at elevated CO pressures (up to 10 Tors dosed onto the sample).…”
Section: Spectroscopic Investigation Of 07 Wt% Pd/ssz-39 Using Ftir mentioning
confidence: 95%
See 2 more Smart Citations
“…11). It was previously shown by us that Pd(II)-NO in SSZ-13 upon CO adsorption selectively forms Pd(II)(CO)(NO) complex [8,11] largely responsible for excellent performance of Pd(II)/SSZ-13 as a low temperature passive NOx adsorber (at 100 ⁰C). However, in this case, we observe the unselective formation of Pd(II)(CO)(NO) even at elevated CO pressures (up to 10 Tors dosed onto the sample).…”
Section: Spectroscopic Investigation Of 07 Wt% Pd/ssz-39 Using Ftir mentioning
confidence: 95%
“…The bands in this region belong to NO chemisorbed on cationic Pd. We have previously shown that although these bands fall in the region typical for linearly adsorbed NO, NO in fact binds with its unpaired electron forming a fully covalent bond with an electron given by Pd(II) [8,13,11]: the formation of the strong covalent Pd-N bond in the bent Pd-N-O fragment is the reason why Pd ions in zeolite can function as low-temperature passive NOx adsorbers, i.e. bind NO at 100 ⁰C and release it above ~200 ⁰C.…”
Section: Spectroscopic Investigation Of 07 Wt% Pd/ssz-39 Using Ftir mentioning
confidence: 97%
See 1 more Smart Citation
“…In order to get further insight into the effect of hydrothermal aging on the NOx storage/release (PNA) properties of aged materials, we performed studies under practically relevant conditions on the fresh and aged samples of 1-3 wt% Pd/SSZ-13 with Si/Al ~6, 12 and 30 as well as 1 wt% Pd/BEA with Si/Al ~12. The samples were prepared according to [35], in order to maximize Pd dispersion.…”
Section: Investigation Of Pna Performance Of Aged 1-3 Wt% Pd/ssz-13 Smentioning
confidence: 99%
“…NOx uptake [35,36,38]. Due to steam-treatment at such high temperatures (750 ºC), dealumination inevitably occurs (see NMR data above).…”
Section: Insight Into the Structural Changes Of Fresh And Hta Pd/ssz-mentioning
confidence: 99%